2020
DOI: 10.5198/jtlu.2020.1424
|View full text |Cite
|
Sign up to set email alerts
|

Where and why do firms choose to move? Empirical evidence from Norway

Abstract: A key goal for many public policies is to increase the competitiveness of local industries and make areas more attractive for firm location and development. However, little is known about firm relocations even though they are of crucial importance in understanding economic development within a region and the effectiveness of the policies proposed. This paper contributes to filling this gap by looking further into the firm relocation process by estimating models for the decision to relocate and to where. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…Іще два новітні мотиви, які спонукають підприємства до релокації, -це процеси агломерації [15,17,18] та військові конфлікти. Зокрема, війна росії проти України є яскравим тому підтвердженням.…”
Section: теоретична концепція ключові фактори метрикаunclassified
See 1 more Smart Citation
“…Іще два новітні мотиви, які спонукають підприємства до релокації, -це процеси агломерації [15,17,18] та військові конфлікти. Зокрема, війна росії проти України є яскравим тому підтвердженням.…”
Section: теоретична концепція ключові фактори метрикаunclassified
“…Питанням комплексного дослідження релокації бізнесу присвячено незначну кількість праць як у вітчизняній, так і в зарубіжній науці, оскільки це явище відносно нове і пов'язане насамперед із практичними аспектами діяльності компаній, тобто в цьому випадку практика господарювання випереджає появу обґрунтованих, доведених теоретичних концепцій. Частина досліджених публікацій розкриває або окремі питання мотивації та причин релокації бізнесу [3,4,[7][8][9][10][11][12][13][14], або механізми релокації на окремих регіональних ринках [2,[15][16][17][18]. У вітчизняній практиці питання вивчення стратегій релокації бізнесу актуалізувались лише з початком вторгнення росії на територію України та набули широкої підтримки протягом останнього року за рахунок розроблення та впровадження державних і міжнародних програм підтримки українського бізнесу [19][20][21][22][23][24].…”
unclassified
“…Investigating the relocation choices of Norwegian firms, Nilsen et al. ( 2020 ) find that agglomeration, urbanization, and highly-skilled labor are variables that play an important role. Bodenmann and Axhausen ( 2012 ) find for Switzerland that relocation choices mainly depend on tax burdens and, to a lesser degree, on the accessibility of regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 2017 ; Morkute and Koster 2018 ; Nilsen et al. 2020 ; Rossi and Dej 2020 ), and taxes (Lee 2006 , 2008 ; Bodenmann and Axhausen 2012 ; Conroy et al. 2016 ; Pan et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Van Dijk and Pellenbarg (2017) pointed out that the spatial scale is important in firm migration, because the causes and the effects differ substantially for firm relocations within urban areas and between regions within countries, and for international relocations between countries or even continents. Nilsen, Tørset, Gutiérrez, Cherchi, & Andersen (2020) indicated that the relocate decision which is influenced by a firm's internal and external characteristics such as agglomerations. Bhat and Guo (2004) proposed a mixed spatially correlated logit (MSCL) model for location-related choices.…”
Section: Literature Reviewmentioning
confidence: 99%